2010
DOI: 10.1159/000276989
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Lymphocyte Apoptosis in Rat Liver Allograft by Adenoviral Gene Transfection of Human Interleukin-10

Abstract: Background/Aims: Gene therapy can provide a possible avenue in organ transplantation to treat acute allograft rejection. This study was designed to investigate the effect of adenovirus-mediated human IL-10 (hIL-10) gene transfer on the apoptosis of infiltrating lymphocytes and examine the efficacy of hIL-10 gene transfer in combination with subtherapeutic doses of cyclosporine A (CsA) in a rat liver transplantation model. Methods: Inbred male DA and LEW rats were used for liver donors and recipients, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Additionally, IL-10 has been shown to be upregulated in human livers [91] and kidneys [164]. Work undertaken by Li et al suggested that IL-10 expression after BD may be important in stimulating apoptosis of graft infiltrating lymphocytes through activation of the Fas/Fas Ligand pathway [165]. There is little published in the literature investigating the role of IL-5 and IL-13 during brain death.…”
Section: Stage Two Of Potential Organ Injury: Brain Deathmentioning
confidence: 99%
“…Additionally, IL-10 has been shown to be upregulated in human livers [91] and kidneys [164]. Work undertaken by Li et al suggested that IL-10 expression after BD may be important in stimulating apoptosis of graft infiltrating lymphocytes through activation of the Fas/Fas Ligand pathway [165]. There is little published in the literature investigating the role of IL-5 and IL-13 during brain death.…”
Section: Stage Two Of Potential Organ Injury: Brain Deathmentioning
confidence: 99%
“…IL‐10 produced by macrophages and Th2 cells has a crucial role in inducing immune tolerance via a variety of mechanisms including inhibiting the secretion of Th1 cell cytokines, and downregulating the expression of MHC II on monocytes and costimulatory molecules on macrophages. Based on these effects, IL‐10 is a candidate immunosuppressive cellular therapy for allograft rejection . In this study, imDCs produced IL‐10 themselves in vitro , and IL‐10 gene transduction boosted the production of IL‐10 more than four times.…”
Section: Discussionmentioning
confidence: 74%
“…The concept that exogenous IL-10 is useful therapeutically to diminish immunopathological disease has been previously examined in settings of transplantation and autoimmune disease (1,32,33). IL-10, delivered via adeno-associated virus or lentivirus vectors, diminishes the rate of graft rejection in several models of organ transplantation, including allogeneic heart, lung, liver, and pancreas transplants (8,11,19,25). IL-10 diminished disease severity in several autoimmune diseases, including mice with experimental autoimmune encephalomyelitis (EAE) (6,7,24,47).…”
Section: Discussionmentioning
confidence: 99%